Efforts of non-communicable disease posbindu as a health-promoting university literacy campaign in the era of adapting to new habits: A case study at Universitas Gadjah Mada - Dilalah, Idlohatud; Bintoro, Bagas Suryo (BKM Public Health and Community Medicine, 2021)
Purpose: Universitas Gadjah Mada (UGM) has a passion for Health Promoting University to improve the health status of its citizens. One of these commitments resulted in the NCD Posbindu as a health literacy activity in the NCD prevention and management. The COVID-19 pandemic requires adjustments to health protocols, including implementing posbindu at UGM. The Faculty of Medicine, Public Health, and Nursing (FK-KMK) UGM is one of the units that carry out posbindu activities in the era of adopting new habits. Documentation related to how the implementation and adjustment of posbindu activities at FK-KMK UGM in the period of adaptation to new habits are essential for program improvement. In addition, the good practice of implementing posbindu can be an example for other work units to initiate and develop posbindu. Contents: Posbindu at FK-KMK UGM is called Posbindu Sehati (prosperous, active, and of high quality). Most posbindu cadres are education personnel who are generally not health workers, so they are given training before posbindu implementation. The community service section of FK-KMK UGM funded this activity's procurement tools and infrastructure. Posbindu Sehati was first held in 2019 in conjunction with healthy exercise activities and regularly planned every three months. The Sehati Posbindu activity, attended by staff and education staff of FK-KMK UGM, was piloted in the new habits era on April 9, 2021, and had only been running three times before the pandemic. The activity information was disseminated using Whatsapp groups and HPU FK-KMK UGM social media. The challenge of implementing posbindu during a pandemic was on health protocols, especially maintaining distance. The queue buildup occurred due to the difference in the duration of service at each table. Inviting posbindu participants in several waves and carrying out on a broader area is recommended to avoid crowds. The manual to electronic record-keeping switch can facilitate data integration into existing systems. Periodic training is recommended to increase the ability and self-confidence of cadres. Tujuan: Universitas Gadjah Mada (UGM) sebagai tempat belajar sekaligus tempat bekerja memiliki semangat menuju Health Promoting University guna meningkatkan derajat kesehatan warganya. Komitmen ini salah satunya diwujudkan melalui posbindu PTM sebagai kegiatan literasi kesehatan dalam pencegahan dan pengelolaan PTM. Pandemi COVID-19 mengharuskan setiap kegiatan diselenggarakan dengan penyesuaian protokol kesehatan, termasuk pelaksanaan posbindu di UGM. Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan (FK-KMK) UGM adalah salah satu unit yang melakukan kegiatan posbindu di era adaptasi kebiasaan baru. Dokumentasi terkait bagaimana pelaksanaan dan penyesuaian kegiatan posbindu di FK-KMK UGM pada era adaptasi kebiasaan baru penting dilakukan untuk perbaikan program. Selain itu, praktik baik pelaksanaan posbindu dapat menjadi contoh bagi unit kerja lain untuk menginisiasi dan mengembangkan posbindu. Isi: Posbindu di FK-KMK UGM disebut dengan Posbindu Sehati (sejahtera, aktif, dan bermutu tinggi). Sebagian besar kader posbindu adalah tenaga kependidikan yang umumnya bukan tenaga kesehatan, sehingga diberikan pelatihan sebelum pelaksanaan posbindu. Kegiatan ini didanai oleh bagian pengabdian masyarakat FK-KMK UGM, namun terbatas untuk pengadaan alat dan sarana-prasarana. Posbindu Sehati pertama kali diadakan pada tahun 2019 bersamaan dengan kegiatan senam sehat dan direncanakan dilakukan setiap 3 bulan sekali. Kegiatan Posbindu Sehati baru berjalan tiga kali sebelum pandemi dan diujicobakan di era kebiasaan baru pada tanggal 9 April 2021. Informasi kegiatan disebarkan melalui grup Whatsapp dan media sosial HPU FK-KMK UGM. Kegiatan diikuti oleh staf dan tenaga kependidikan FK-KMK UGM. Tantangan pelaksanaan posbindu saat pandemi adalah pada protokol kesehatan, terutama menjaga jarak. Penumpukan antrian tetap terjadi meskipun sudah diantisipasi karena perbedaan durasi pelayanan pada setiap meja. Rekomendasi untuk menghindari kerumunan dapat dilakukan dengan mengundang peserta posbindu dalam beberapa gelombang dan dilakukan di area yang lebih luas. Penggantian pencatatan manual ke elektronik dapat memudahkan integrasi data ke sistem yang sudah ada. Pelatihan berkala direkomendasikan guna meningkatkan kemampuan dan rasa percaya diri kader.